CASE REPORT ON A PATIENT WITH CHRONIC KIDNEY DISEASE STAGE V WITH IMPAIRED PHYSICAL MOBILITY AT RSUP DR SARDJITO YOGYAKARTA - Puspitasari, Tarissa Widhi; Setiawati, Estriana Murni (Indonesian Journal of Community Health Nursing, 2025)
Introduction: Chronic Kidney Diseases (CKD) is a problem that occurs in decreased kidney function where the kidneys cannot maintain the body's metabolic, fluid and electrolyte balance. CKD affects the ability of the kidneys to produce the hormone erythropoetin, which affects the function of oxygen distribution into cells for metabolism. Disruption of oxygen supply affects motor function making limbs experience weakness and decreased muscle strength. This study aims to describe a case study of a stage 5 CKD patient with impaired physical mobility. Method: The method in this report uses a descriptive case design with a case study approach in CKD stage 5 patients. Conclusion: The conclusion in this report is that the patient experienced complications of the disease so that the improvement of physical mobility with passive ROM could not be seen within 3 days. Further research is needed regarding the effectiveness of the interventions used in similar conditions as a comparison of the success of the interventions provided. Keywords: Renal failure, Physical mobility impairment, Passive ROM, Palliative.